Willingness to pay for livestock insurance by dairy farmers in Kavrepalanchowk district, Nepal - Sita Acharya; Ujjal Tiwari; Rishi Ram Kattel; Shiva Chandra Dhakal (Cogent Food & Agriculture, 2024)
Dairy production is one of the risky businesses, which seeks effective risk management strategies. Adoption of a livestock insurance scheme is one of the most effective risk management strategies for dairy entrepreneurs. However, in Nepal, insurance coverage is very low in the dairy sub-sector. The study aimed to assess the dairy farmer’s willingness to pay for the livestock insurance scheme. The study was carried out in Kavrepalanchowk district of Nepal in 2022. The simple random sampling technique was used to select 146 dairy farmers. Double Bounded Dichotomous Choice Contingent Valuation technique was used to estimate Willingness to Pay (WTP). About 93% of the respondent farmers were the member of cooperatives which was the major source of information flow for livestock insurance scheme to them. The result revealed that number of cattle reared, awareness about livestock insurance scheme, and experience of livestock loss have significant positive influences in the decision regarding the adoption of livestock insurance. Farmers are willing to pay more than the current premium rate for livestock insurance. Hence, only increasing the subsidy might not be the solution in expanding the livestock insurance adoption rate. Rather, alternative approach like mobilizing institutions (cooperative) in expanding the insurance scheme is required.